Patterns of developmental regression and associated clinical characteristics in SLC6A1-related disorder - Kalvakuntla, Sanjana; Lee, MinJae; Chung, Wendy K.; Demarest, Scott; Freed, Amber; Horning, Kyle J.; Bichell, Terry Jo; Iannaccone, Susan T.; Goodspeed, Kimberly (Frontiers in Neuroscience, 2023)
SLC6A1-related disorder is a genetic neurodevelopmental disorder that is caused by loss of function variants in the SLC6A1 gene. Solute Carrier Family 6 Member 1 (SLC6A1) gene encodes for gamma-aminobutyric acid (GABA) transporter type 1 (GAT1), which is responsible for reuptake of GABA from the synaptic cleft. Tight regulation of GABA levels plays an important role in brain development by balancing inhibitory and excitatory neuronal signaling. Consequently, individuals with SLC6A1-related disorder can have manifestations such as developmental delay, epilepsy, autism spectrum disorder, and a subset have developmental regression. In this study, we identified patterns of developmental regression among a cohort of 24 patients with SLC6A1-related disorder and assessed for clinical characteristics associated with regression. Individuals with developmental regression had a loss of skills that were previously mastered in developmental domains including speech and language, motor, social, and adaptive skills. We reviewed medical records of patients with SLC6A1-related disorder and divided subjects into two groups: 1) regression group and 2) control group. We described the patterns of developmental regression including whether there was a trigger prior to the regression, multiple episodes of regression, and whether or not skills were recovered. We assessed the relationship of clinical characteristics among the regression and control groups including demographic factors, seizures, developmental milestone acquisition, gastrointestinal problems, sleep problems, autism spectrum disorder, and behavioral problems. The mean age at regression was 2.7 years and most subjects had regression of language or motor skills triggered by seizures, infection, or spontaneously. Although there was no significant difference in clinical characteristics between the two groups, there was a higher prevalence of autism and severe language impairment in the regression group. Future studies of a larger cohort of patients are required to make definitive conclusions. Developmental regression is often a sign of severe neurodevelopmental disability in genetic syndromes, but it is poorly understood in SLC6A1-related disorder. Understanding the patterns of developmental regression and the associated clinical characteristics in this rare disorder will be important to medical management, prognostication, and could impact the design of future clinical trials.